Fossil Corals With Various Degrees of Preservation Can Retain Information About Biomineralization-Related Organic Material - Drake, Jeana L.; Guillermic, Maxence; Eagle, Robert A.; Jacobs, David K. (Frontiers in Earth Science, 2021)
Scleractinian corals typically form a robust calcium carbonate skeleton beneath their living tissue. This skeleton, through its trace element composition and isotope ratios, may record environmental conditions of water surrounding the coral animal. While bulk unrecrystallized aragonite coral skeletons can be used to reconstruct past ocean conditions, corals that have undergone significant diagenesis have altered geochemical signatures and are typically assumed to retain insufficient meaningful information for bulk or macrostructural analysis. However, partially recrystallized skeletons may retain organic molecular components of the skeletal organic matrix (SOM), which is secreted by the animal and directs aspects of the biomineralization process. Some SOM proteins can be retained in fossil corals and can potentially provide past oceanographic, ecological, and indirect genetic information. Here, we describe a dataset of scleractinian coral skeletons, aged from modern to Cretaceous plus a Carboniferous rugosan, characterized for their crystallography, trace element composition, and amino acid compositions. We show that some specimens that are partially recrystallized to calcite yield potentially useful biochemical information whereas complete recrystalization or silicification leads to significant alteration or loss of the SOM fraction. Our analysis is informative to biochemical-paleoceanographers as it suggests that previously discounted partially recrystallized coral skeletons may indeed still be useful at the microstructural level.